Perawatan luka terhadap pencegahan infeksi pada tali pusat di Klinik Barokah Medika - Nurhayati, Nurhayati; Aliun, Fatimah Wahab; Suharti, Sri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2024)
Background: Umbilical cord wound care is carried out as an act of caring for and cleaning the umbilical cord, as well as preventing infection in the baby's umbilical cord and speeding up the healing of wounds left by cutting the umbilical cord. Providing nursing in the form of education to mothers about how to properly care for the umbilical cord can prevent infection in newborns according to independent nursing practice service standards. Purpose: to prevent tetanus in newborn babies, so that the umbilical cord Method: Case study research on nursing care for newborns uses descriptive observational methods. This research was conducted at the Barokah Medika Clinic, independent practice nurse Dr. Siroojudin, SP. Og. which is located in Sumberejo village, Kemiling Bandar Lampung District on February 20 2023. The intervention carried out was in the form of providing education on care and prevention of infection in the baby's umbilical cord to two mothers who had 4 day old babies. Results: The results of the baby's examination, Mrs. S and Mrs. A, when making his first visit to the Barokah Medika clinic on February 20 2023 at 10.00 WIB, was stated to be in general condition and within normal limits with good general condition examination results, compensatory awareness, N = 116 x/m, RR= 45 x/m, and S=36.5◦ C. Based on the stages of baby umbilical cord care that have been carried out, the baby's mother only observes and tries to understand the explanation that has been given. So he said he would apply it himself when he got home and felt lucky because he had increased knowledge in umbilical cord care. Conclusion: Improper care for umbilical cord wounds in babies will result in infection which can result in death. Basically, umbilical cord infections can be prevented by carrying out good and correct umbilical cord care, namely using the principles of dry and clean care. Suggestion: nurses can provide complete information about how to care for umbilical cord wounds in mothers who have newborn babies properly and correctly to prevent infections in babies. Apart from that, it is important for mothers of babies to know how to care for umbilical cord wounds so that mothers can do it independently without having to feel awkward, afraid and worried about making mistakes in carrying out umbilical cord care.                                                 Keywords: Infection; Umbilical Cord; Wound Care.   Pendahuluan: Perawatan luka tali pusat dilakukan sebagai tindakan merawat dan membersihkan tali pusat, serta mencegah terjadinya infeksi pada tali pusat bayi dan mempercepat penyembuhan luka bekas pemotongan tali pusat. Menyediakan keperawatan berupa edukasi kepada ibu tentang cara merawat tali pusat yang benar dapat mencegah infeksi pada bayi baru lahir sesuai standar pelayanan praktik mandiri keperawatan. Tujuan: untuk mencegah penyakit tetanus pada bayi baru lahir, sehingga tali pusat tetap bersih,kuman tidak masuk sehingga tidak terjadi infeksi pada tali pusat bayi. Metode: Penelitian studi kasus asuhan keperawatan pada bayi baru lahir menggunakan metode deskriptif observasional. Penelitian ini dilakukan di Klinik Barokah Medika perawat praktik mandiri Dr. Siroojudin, SP. Og. yang terletak di desa Sumberejo, Kecamatan Kemiling Bandar Lampung pada tanggal 20 Februari 2023. Intervensi yang dilakukan berupa pemberian edukasi perawatan dan pencegahan infeksi pada tali pusat bayi pada Ny. S dan Ny. A yang memiliki bayi umur 4 hari. Hasil: Hasil pemeriksaan bayi Ny. S dan Ny. A pada saat melakukan kunjungan pertama di klinik Barokah Medika pada tanggal 20 Februari 2023 pukul 10.00 WIB dinyatakan dalam keadaan umum dan batas normal dengan hasil pemeriksaan keadaan umum baik, kesadaran komposmenti, N = 116 x/m, RR= 45 x/m, dan S=36.5◦ C. Berdasarkan tahapan perawatan tali pusat bayi yang telah dilakukan, ibu bayi hanya mengamati dan mencoba memahami penjelasan yang telah berikan. Sehingga mengatakan akan mengaplikasikannya sendiri jika sudah sampai di rumah dan merasa beruntung karena bertambah ilmu dalam perawatan tali pusat. Simpulan: Perawatan luka tali pusat pada bayi tidak tepat akan mengakibatkan infeksi yang dapat mengakibatkan kematian. Infeksi tali pusat pada dasarnya dapat dicegah dengan melakukan perawatan tali pusat yang baik dan benar, yaitu dengan prinsip perawatan kering dan bersih. Saran: perawat dapat memberikan informasi yang lengkap tentang cara merawat luka tali pusat pada ibu yang memiliki bayi baru lahir dengan baik dan benar sebagai pencegahan infeksi pada bayi. Selain itu, penting bagi ibu bayi untuk mengetahui cara perawatan luka tali pusat sehingga ibu dapat melakukannya secara mandiri tanpa harus ada rasa canggung, takut, dan khawatir akan mengalami kesalahan dalam melakukan perawatan tali pusat.   Kata Kunci: Infeksi; Perawatan Luka; Tali Pusat.